MODEL PEMBELAJARAN TIK UNTUK MENINGKATKAN PENGATURAN DIRI DALAM BELAJAR SISWA - Sri Mardiyati (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract: In anticipation of the development of technology that students need to be equipped with adaptive capabilities to anticipate changes. Subjects Tekonologi Information and Communication one of them is to anticipate the needs. Interpreted in the field of ICT with computer lessons taught specific software. This study aims to find a model of learning that enable students to develop the Self in Learning Settings.  The resulting model consists of five stages of opening, material, training, evaluating and integrating activities that cover students, teachers and multimedia support. Based on the results of statistical tests for differences early test scores and final test in the experimental group and the control group, found learning model with self-regulation in learning better than the usual model of learning. Keywords: Models of Learning, Student Self Settin